Latin American South-South integration and cooperation : from a regional public goods perspective - Kuwayama, Mikio (ECLAC SantiagoCL, 2005)
Examines South-South trade. Looks at the proliferation of preferential trade agreements and South-South trade. Focuses also on the deep integration agenda and South-South Agreements.